THE INFLUENCED OF GOOD CORPORATE GOVERNANCE TO CORPORATE SUSTAINABILITY - Vienda A Kuntjoro (International Conference On Law, Business and Governance (ICon-LBG), 2016)
The purposed of this researched is to know the influenced of good corporate governance to corporate sustainability. The data was taken from 30 manufacturing companies and 15 mining companies. The regression analysis will be used in this researched. The result showed that good governance as dependent variable influenced positively and significant to corporate sustainability. T result only had small number of R squared so it might say that there was another variables that could influenced to corporate sustainability.